Developmental trajectories of maternal fear of childbirth at different times: a prospective longitudinal study - Qian Jing; Jiang Jie; Xu Ke; Yang Liu; Deng Xiumin; Li Xiuchuan; Li Jinzhi (BMC Women's Health)
Abstract Objective This study aims to uncover the trend of maternal fear of childbirth and its influencing factors in China through a prospective longitudinal study. Methods Between November 2022 and March 2023, 229 pregnant women were selected through convenience sampling in a Grade 3 A hospital in Bengbu as study subjects for a prospective longitudinal study. The study subjects completed the W-DEQ A questionnaire to assess their prenatal fear of childbirth in early, mid, and late pregnancy, and the W-DEQ B questionnaire to assess their postnatal fear of childbirth in the postpartum period, and finally, the data were compiled and analyzed by using one-way analysis of variance, latent category growth model, and multivariate logistic regression analysis. Results The developmental trajectories of 229 pregnant women’s fear of childbirth at different times could be categorized into three latent categories, which were Persistent severe fear of childbirth group (12.7%), Persistent high fear of childbirth group (73.8%), and Stabilized moderate fear of childbirth group (13.5%). The number of deliveries, desired mode of childbirth, and prenatal education were the factors influencing the developmental trajectory of maternal fear of childbirth (P < 0.05). Conclusion Heterogeneity exists in the developmental trajectory of maternal fear of childbirth, and healthcare providers can individualize interventions according to the categories of the trajectory of fear of childbirth and their influencing factors.